Multidimensional Approach Toward Spiritual Coping: Construction and Validation of the Spiritual Coping Questionnaire (SCQ) - Charzyńska, Edyta (Journal of religion and health, 2015)
The aim of the research was to construct the Spiritual Coping Questionnaire (SCQ). Two studies have been carried out: the first on the sample of 1,296 persons facing stressful situations, and the second, on 352 persons undergoing alcohol addiction therapy. The first study provided data for PCA and CFA, calculation of internal consistency, test-retest reliability and descriptive statistics of the questionnaire. The second study allowed the author to verify the construct and criterion validity of the tool. The final version of the SCQ is composed of 32 items constituting two scales: positive and negative spiritual coping. The scale of positive spiritual coping includes four subscales—domains (personal, social, environmental and religious), and the scale of negative spiritual coping, three subscales (personal, social and religious). The validity and reliability of the tool are satisfactory. The questionnaire can be used to measure spiritual coping, both among religious and non-religious people.